2020
DOI: 10.1021/acs.oprd.0c00216
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Scalable Synthesis and Process for EMA401, Part II: Development and Scale-Up of a Pyridine- and Piperidine-Free Knoevenagel–Doebner Condensation

Abstract: During route scouting for EMA401 (1), an angiotensin II type 2 antagonist, we identified the synthesis of key amino acid intermediate 2 via its cinnamic acid derivative 3 as a streamlined option. In general, cinnamic acids can be synthesized from the corresponding aldehydes by a Knoevenagel−Doebner condensation in pyridine with piperidine as an organocatalyst. We aimed to replace both of these reagents and found novel conditions involving toluene as the solvent and morpholine as the organocatalyst. Scale-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Due to the issues observed in the isolation of ketoacid 28 , we turned our attention to an alternative biocatalytic system and identified the phenylalanine ammonia lyase (PAL) catalyzed synthesis of amino acid 2 as a very attractive alternative in terms of safety, ecology, and economy. These findings are disclosed in parts II and III of this publication series. , …”
Section: Results and Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Due to the issues observed in the isolation of ketoacid 28 , we turned our attention to an alternative biocatalytic system and identified the phenylalanine ammonia lyase (PAL) catalyzed synthesis of amino acid 2 as a very attractive alternative in terms of safety, ecology, and economy. These findings are disclosed in parts II and III of this publication series. , …”
Section: Results and Discussionmentioning
confidence: 52%
“…These findings are disclosed in parts II and III of this publication series. 20,21 Investigations on the Theoretical Impurity Bis-(chloromethyl) ether. Bis(chloromethyl) ether (BCME; CAS #542-888-1) is a highly toxic compound and known mutagen, classified as an ICH M7 class 1 impurity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A streamlined manufacturing process afforded the substrate, cinnamic acid 2 , with a morpholine content of around 4–5 mol % . Use tests and screenings showed that morpholine in 2 was not critical and that up to 10 mol % morpholine did not have an impact on the conversion (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…For the preparation of amino acid 3 via the chemocatalytic route, aldehyde 5 was treated with Horner–Wadsworth–Emmons reagent 6 to obtain enamide 7 , which was subjected to asymmetric hydrogenation conditions to afford amide 8 , followed by functional group interconversion to give carbamate 9 and finally deprotection to yield amino acid 3 . The synthetic approach using the biocatalytic route described in this publication requires only two stages to obtain the key intermediate 3 starting from 5 , which was reacted to give cinnamic acid 2 followed by PAL-catalyzed hydroamination to furnish amino acid 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation